Conduct Disorder, War Zone Stress, and War-Related Posttraumatic Stress Disorder Symptoms In American Indian Vietnam Veterans - Dillard, Denise (2007)
This study examined whether conduct disorder (CD) was associated with war zone stress and war-related post-traumatic stress disorder (PTSD) symptoms in American Indian (AI) Vietnam veterans. Cross-sectional lay-interview data was analyzed for 591 male participants from the American Indian Vietnam Veterans Project. Logistic regression evaluated the association of CD with odds of high war zone stress and linear regression evaluated the association of CD and PTSD symptom severity. Childhood CD was not associated with increased odds of high war zone stress. CD was associated with elevated war-related PTSD symptoms among male AI Vietnam Veterans independent of war zone stress level and other mediators. Future efforts should examine reasons for this association and whether the association exists in other AI populations.